Relationship between Recalled Parental Care and Religious Coping: The Mediating Effect of Attachment to God - Láng, András (European Journal of Mental Health, 2016)
Attachment to God is related to both parental bonding and religious coping, but the relation of the two latter variables has gained little attention until now. In a study among 95 Roman Catholics (49 women), the mediating role of attachment to God between perceived parental care and religious coping was tested. Results showed that levels of avoidant attachment to God and positive religious coping were independent of perceived parental care. Multiple linear regressions revealed that anxious attachment to God fully mediated the relationship between parental care and negative religious coping. Possible explanations for these selective relationships are discussed.